Meister Eckhart : Analogy, Univocity and Unity. Translated with a Preface and an Appendix by Orrin F. Summerell. - Mojsisch, Burkhard (John Benjamins Pub. Co., 2001)
The thought of Meister Eckhart -- the Dominican theologian, the preacher, the master of language, the mystic -- exudes a remarkable fascination on the modern mind, not the least due to its characteristic interplay of scholastic-academic and vernacular terminology. This volume presents the only book-length study in English of Meister Eckhart the philosopher within the tradition in which his thought is embedded and from which it draws its authority. It shows that even as Eckhart may be justly regarded as a medieval precursor of a modern philosophy of subjectivity, the novelty and continuity of his.